Banking reform and financial sector development in Central and Eastern Europe and EU Accession Countries - Hagmayr, Bettina; Haiss, Peter (Univerzita Pardubice, 2006)
From the empirical evidence on the finance-growth-nexus in European transition countries, we conclude that financial sector reform, especially of the banking sector, can contribute to economic growth and speed up transition. Empirical research by Cottarelli, Dell´Arriccia and Vladkova-Hollar (2005) and others has provided evidence that factors originating in the banking system, rather than the corporate sector, were responsible for growth differences in accession and transition economies. In extending the conventional finance-growth framework and based on observations in New EU-Member States (NMS), we suggest that strong foreign bank investment and related cross-border credit from parent banks may have been a substitute for domestic bank growth and thus in supporting real sector growth in South-Eastern Europe (SEE). Given the massive-scale involvement of foreign banks in NMS and SEE, more research is necessary in this area. In SEE countries, economic and bank transition started later than in NMS because of political circumstances. As evident from the experience in NMS, financial development is not growthsupportive when the institutional and legal framework given to market participants is not appropriate. Unsound banking intermediation has a direct impact on economic growth as such behaviour perpetuates economic stagnation and inefficient use of resources. Unsound financial sectors in SEE also indirectly hamper economic growth, as they pose serious obstacles to inflows of foreign direct investment which in turn would contribute to economic growth. When financial institutions are subject to poor governance and incentive structures, finance can hardly promote growth. Instead of supporting growth, granting bad loans back to companies of their owners, for example, leads to resource misallocation, reduced private sector confidence and results in lower investment and growth. Policies thus should continue to focus on alleviating the bottlenecks to financial intermediation by guaranteeing stable macroeconomic conditions and a sound institutional legal and supervisory environment. The involvement of foreign banks is found to be a major factor for stabilizing the banking sector and making it fit to support economic growth.
Keywords: banking reform; financial sector; economic growth; transition countries; accession countries